Educational challenges in virtual environments: rural and urban schools - Meléndez Grijalva, Perla (2021)
The results of an investigation that investigated the perceptions and experiences of university students in urban and rural contexts are presented, in order to know how they live their education in a virtual mode under a pandemic context, considering three categories: pedagogical, material and emotional It was a qualitative study based on the phenomenological method, in-depth interviews and documentary analysis were applied. Twelve university students from rural areas and 15 from urban areas in the State of Chihuahua participated. The results indicate that in both contexts a deficient education was perceived, with traditional and boring teaching practices, with lower than expected learning and ineffective feedback and communication; low motivation and recurrent feelings of fear, sadness and hopelessness were presented. The greatest concern in urban contexts was the risk of contagion and social isolation, in rural the problems of connectivity and economic poverty. Regarding material resources, students in rural contexts had greater deficiencies, less than half had a computer and internet. On the other hand, it was found a development of technological skills and self-management of learning such as time and resource management, the organization of activities and the self-construction of knowledge. It is concluded that virtual education is developed under a traditional paradigm, which makes it necessary to strengthen not only access to technologies, but also to promote motivation, participation and interactions among students and transform passive practices through organized, flexible experiences with social impact, attitudinal and cognitive.